The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pone.0280313
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and coping strategies among resident physicians at an Indonesian tertiary referral hospital during COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has increased the burden on resident physicians. They may use different coping strategies to manage those burdens, which partly determine their mental health outcomes, including burnout syndrome. This study explores the relationship between coping strategies and burnout among resident physicians during the COVID-19 pandemic in an Indonesian tertiary referral hospital. Methods This online cross-sectional study was conducted from June to August 2020, involving nine residency pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
2
5
0
2
Order By: Relevance
“…Encouragingly, the most frequently reported coping strategies by doctors in Ireland were adaptive rather than maladaptive , and this finding was consistent across grades and sexes. This is in keeping with several international studies12 28 29 but is in contrast to a UK study 3…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Encouragingly, the most frequently reported coping strategies by doctors in Ireland were adaptive rather than maladaptive , and this finding was consistent across grades and sexes. This is in keeping with several international studies12 28 29 but is in contrast to a UK study 3…”
Section: Discussionsupporting
confidence: 91%
“…A study of doctors in the UK3 found that the most frequently reported coping mechanism was the maladaptive strategy of self-distraction (ie, drawing one’s thoughts or attention away from the problem or stressor). In contrast, recent studies of Italian healthcare workers12 and residents in Indonesia28 found that the most commonly reported coping strategies were adaptive . Similarly, a cross-cultural study found that the most commonly reported coping strategies by German and Australian doctors were the adaptive strategies of active coping, planning and positive reframing 29…”
Section: Introductionmentioning
confidence: 83%
“…Interventions should focus on promoting healthier coping mechanisms to prevent and alleviate burnout. Existing literature support these findings, as studies in other settings have demonstrated similar associations between dysfunctional coping and elevated burnout levels among healthcare professionals ( 26 ). However, it would be valuable to explore dissenting views or alternative coping strategies to ensure a comprehensive understanding of the relationship between coping mechanisms and burnout in this specific context.…”
Section: Discussionsupporting
confidence: 56%
“…Using self- distraction as a coping mechanism has been reported as one of the most used coping strategies among medical residents globally and is considered a maladaptive approach. 27 , 28 Studies have also suggested that residency training is a time of heightened vulnerability associated with mental exhaustion and suppressed emotions. 12 A study looking at the impact of emotional regulation on burnout reported that emotional suppression was associated with higher burnout and depersonalization and was also considered maladaptive.…”
Section: Discussionmentioning
confidence: 99%